IbM Sentra Pengolahan Ikan Lele - Hedher Tuakia; Sherly Hesti Erawati (Jurnal ABM Mengabdi, 2014)
The village Mojolangu Lowokwaru District Malang, especially around Jalan Sudimoro which became a place of business Processing Partners catfish is a flat area with the economic conditions of the people who belong to underprivileged. People's livelihood, among others: farmers, labors, merchants, farm labors, carpenters, masons, and other informal sectors. The existence of catfish management provides many benefits to the surrounding community, because they can get involved in the management of catfish are occupied by business partners. Catfish or catfish is a freshwater fish that has been widely known to the public, catfish farming increasingly mushrooming. Currently there are many people who only process by frying catfish, smoked. But apparently, catfish can be developed in various forms of presentation. With a touch of simple processing diversified technology, catfish can be processed into various food products relatively more durable, with raw materials are cheap and easy way pengolahannyapun. This processing can be expected diversification diversify catfish taste, so as to encompass the broader consumer and can increase the sale value of catfish. Thus, treatment lelepun can create jobs for catfish farmers that will increase revenue and improve the welfare of the family.If the science and technology program for the community catfish processing can be done, it will be able to absorb the labor communities, reduce poverty and unemployment, reduce social inequalities space, and managers will be better catfish. Availability of jobs is part of efforts to create harmony in the life of the surrounding community, as well as the creation of an atmosphere that is safe and secure life.